A gestão do território no SUAS em Niterói: entre a descentralização político-administrativa e a centralidade do território - Pereira, Isadora de Souza Modesto (2020)
This thesis aims to analyze to what extent the territory influences the management and implementation of the Social Assistance policy in Niterói (Rio de Janeiro Brazil) in its multiple scales, also observing its correlation with the political administrative decentralization process of the Brazilian federative system, having as empirical source the management of the Unified Social Assistance System (Sistema Único da Assistência Social SUAS) in the municipality of Niterói, more specifically the Basic Social Protection (Proteção Social Básica PSB) and the Reference Centers of Social Assistance (Centros de Referência da Assistência Social CRAS). To this end, the historical construction of the political administrative decentralization process of the Brazilian federative pact was rescued and the journey through the territory category was made as lived space. We sought to identify how this category is presented in some official documents related to the Social Assistance policy, as well as in the management instruments of the Municipal Departament of Social Assistance and Human Rights of Niterói and in the speech of the workers responsible for the management and provision of the Basic Social Protection services. In this way, the paths chosen by the research allowed successive approximations around the interfederative relations, going through the categories and normative of the Social Assistance policy that gravitate over these relationships, reaching the scale of management in the daily life of the territories, in which such relations concretely affect the provision of social assistance services